St. Vincent And The Grenadines : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2014)
This paper presents the Staff Country Report on St. Vincent and the Grenadines. This Statistical Appendix for St. Vincent and the Grenadines was prepared by a staff team of the IMF as background documentation for the periodic consultation with the member country. It is based on the information available at the time it was completed on December 8, 2006. The views expressed in this document are those of the staff team and do not necessarily reflect the views of the government of St. Vincent and the Grenadines or the Executive Board of the IMF. The policy of publication of staff reports and other documents by the IMF allows for the deletion of market-sensitive information.